PELAKSANAAN PERLINDUNGAN HUKUM BAGI PEKERJA WANITA YANG BEKERJA PADA MALAM HARI DI HARD ROCK CAFE KABUPATEN BADUNG - Satwasti Sugita, Nittya; Markeling, I Ketut; Sandi Sudarsana, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014)
The study is titled "Implementation of the Law for the Protection of Women Workers Working at Night in Hard Rock Cafe Badung regency". This paper aims to find out in depth about the implementation of the law protection and factors that affect the implementation of the legal protection for women workers who work at night at Hard Rock Cafe Badung regency. This type of research is empirical legal research, which examines issues or facts occurring in the field is based on legislation. Techniques of data collection using observation, interview, and documentation. In this case the owner or entrepreneur café is quite effective to implement the provisions stipulated in the Indonesian Republik act number 13 of 2003 but one thing that can not be implemented, namely the shuttle vehicle which is in fact on the ground most of the workers themselves who objected to the rule.
Keywords: law protection, women workers, working at night